PERAN PEMERINTAH DAERAH DALAM PEMBERDAYAAN PETERNAK KAMBING KALIGESING DI KABUPATEN PURWOREJO (STUDI KASUS DI KECAMATAN KALIGESING KABUPATEN PURWOREJO) - Nurul Istiqomah; Achmad Taufiq (Journal of Politic and Government Studies, 2019)
This research was conducted with background of the government policy of Purworejo District through the Agrieculture Food Marine and Fisheries service. In the effort to realize the empowerment of Kaligesing goat Farmers in Purworejo District, policies were realized and efforts from government for benefits of Kaligesing goat farmers that spread around Purworejo District and incorporated in livestock farmers group of Kaligesing goat farmers. This study research focused on implementing livestock field. This research is using qualitative research methods that refer to the descriptive type. This research subject isthe parties that involved in the implementation of the policy to Kaligesing goat farmers that incorporated in the Kaligesing goat livestock group including agriculture food marine and fisheries service of Purworejo District. The technique of collecting data through observation , interviews, documentation, literature and then analyzed through data reduction techniques, data presentation and verification/draw conclusions. The results of this study indicate that the implementation support to the farmer groups of Kaligesing goats has not been maximized in increasing livestock productivity effectively, that matter because of the difficulty to change the mindset of the farmers and lack of guidance due to technical development of livestock business. To improve the policy, of course there should be complements both administratively and technically. Aid from farmers can be added, intensiveness form agriculture food marine and fisheries related to livestock field, maximizing the control system, and improving infrastructure Keywords : Effectiveness, Policy, Empowering, Farmers, Kaligesing Goat